A diet enriched in longer chain omega-3 fatty acids reduced placental inflammatory cytokines and improved fetal sustainability of C57BL/6 mice. (October 2018) - Akerele, O.A.; Cheema, S.K.
Highlights: Omega (n)-3 polyunsaturated fatty acids (PUFA) are important regulators of inflammatory response that may impact pregnancy outcome. Fish oil based (FO) diet increased the incorporation of longer chain n-3 PUFA into the placenta, and decreased the concentration of pro-inflammatory cytokines. FO diet increased the mRNA expression of placental specific PUFA transporter, which coincided with accretion of n-3 PUFA in fetal brain. FO diet altered the levels of cytokines at different stages of pregnancy. Diet induced alterations in reproductive tissues fatty acid composition and cytokines levels may influence fetal sustainability. Abstract: Omega (n)-3 polyunsaturated fatty acids (PUFA) are important regulators of inflammatory response that may impact pregnancy outcome. The effects of breeding chow diets containing n-3 PUFA from either fish oil (FO) or soybean oil (SO) were investigated on tissue fatty acid composition, inflammatory cytokines and pregnancy outcome. Female C57BL/6 mice (7 weeks old) were fed FO or SO diets for 2 weeks before mating and throughout pregnancy. Animals were sacrificed before and during pregnancy at day 6.5, 12.5 and 18.5. The FO diet increased the incorporation of n-3 PUFA in placenta, with a concomitant decrease in the concentration of pro-inflammatory cytokines. The FO diet increased the mRNA expression of placental specific PUFA transporter, which coincided with accretion of n-3 PUFA in fetal brain. Sites of fetal resorption were noticeable in the SO group but not in the FO group. N-3 PUFA may improve fetal sustainability via altering cytokine levels.